Capillary-Cavernous Hemangioma of Lymph Node: An Extremely Rare Case - Dinata, I Gede Surya; Jatiluhur, Made (JBN (Jurnal Bedah Nasional); Vol 5 No 1 (2021): JBN (Jurnal Bedah Nasional)DO - 10.24843/JBN.2021.v05.i01.p04, 2020)
Background: Hemangioma is a benign vascular tumour commonly found in young children. This tumor can grow within many organs, but occurring in the lymph node is extremely rare. The capillary-cavernous hemangioma (CCH) of the lymph node was mostly found as an incidental finding after histopathology confirmation of oncological surgery. Case: We presented the first case of intranodal CCH from the parietal region of the head in a 11-year-old boy. The easily-bleed lump was found above the head fascia and confirmed with histopathological examination. Conclusion: The capillary-cavernous hemangioma arising from the lymph node was an extremely rare pathological finding after oncological surgery. Treatment by surgical excision was curative. The awareness of this benign vascular tumour must be known to physicians so that it was not mistakenly diagnosed as a malignant disease with subsequent unnecessary radical therapy.